A socio-ecological assessment of land-based contamination and pollution: The Magdalena delta, Colombia - Gallo-Vélez, David; Restrepo, Juan Camilo; Newton, Alice (Frontiers in Marine Science, 2022)
River mouth systems, such as estuaries and deltas are important earth system transitional zones linking the land and coastal marine systems. They funnel anthropogenic contaminants and pollutants from the activities in the river catchment into the marine environment. The present study is focused on the Magdalena River-mouth at Bocas de Ceniza where land-based contamination and pollution are important issues. These were subsequently analysed using an expanded DPSIR framework (Drivers Pressures, State, Impacts Responses). Based on export coefficients and secondary information, the loads of BOD, TSS, Nutrients and solid waste from different sources were identified and compared to prioritize their management within the study area. Findings suggest that contaminants generated in the study area may be insignificant compared to the inputs from the Magdalena River, but they can have a significant impact on the state of local ecosystems. Of all the sources analysed, agriculture and livestock are theoretically the largest contributors of nitrogen (i.e., 14.84 t d-1 and 48.99 t d-1) and phosphorus (i.e., 5.90 t d-1 and 19.46 t d-1) in the basin ‘Direct to the Caribbean’ and ‘Cienaga de Mallorquín’ (that altogether are identified as DtC+) and the ‘Western bank of the lower Magdalena’ (DtM-LM), respectively. In the case of BOD, domestic and industrial wastewaters contribute about 5.10 t d-1 and 98.43 t d-1 in the same basins. Contributions of faecal coliforms were more than 4 orders of magnitude higher in untreated wastewater, being 4.86 x1016 NMP d-1 and 1.78 x1016 NMP d-1 in the lower Magdalena and Caribbean catchments, respectively. Inadequately managed waste and plastic represent a serious problem for the Caribbean Basin. Solid waste generated within the study area and coming from the Magdalena basin and the Caribbean Sea, reaches the coast and deteriorates its visual quality, affects mangrove ecosystems, and generates impacts on coastal populations. By basin, the DtM-LM is where the greatest pollutant loads are generated. However, in terms of impact on human well-being, it is the DtC+ that bears the brunt where pressures are translated in impacts such as increased maintenance and cleaning cost of beaches, reduction or loss of tourism revenue, adverse health effects to vulnerable groups, reduce protection against natural hazards, increased living costs and loss of cultural values.